Autonomous System for Observation of QoS in Telecommunications Networks - Kajackas, A.; Batkauskas, V.; Saltis, A.; Gursnys, D. (Elektronika ir Elektrotechnika, 2011)
A project of creation of a multi-dimension and autonomous QoS evaluation and monitoring system is presented in the paper. The initial data for evaluation of the QoS is collected from users using specially created software programs - iQoS modules. Singularities of the initial data collection are discussed. Test results of the prototype system are presented. Ill. 2, bibl. 14 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.347